SAVI and Contextual Problems as Science Learning Strategies that Enhance Critical Thinking and Learning Motivation - Dewa Made Riyan Gunawan; Nyoman Dantes; I Made Ardana (Universitas Pendidikan Ganesha, 2025)
Science learning in elementary schools still tends to be oriented towards low-level thinking skills, so that students' critical thinking skills and learning motivation have not developed optimally. This study aims to analyze improvements in students' critical thinking skills and learning motivation through the application of the SAVI learning model, oriented to contextual problems in science content. This study is quantitative, with a quasi-experimental pretest–posttest control-group design. The subjects were 63 fourth-grade students, divided into an experimental group of 32 and a control group of 31. Data collection was carried out using both test and non-test methods, with instruments comprising multiple-choice tests to measure critical thinking skills and questionnaires to measure student learning motivation. The data were analyzed using descriptive and inferential statistics via Multivariate Analysis of Variance (MANOVA) at the 5% significance level. The results of the study indicate that applying the SAVI learning model, oriented to contextual problems, significantly improves students' critical thinking skills and learning motivation, in line with the research objectives. The conclusion of this study confirms that learning that integrates somatic, auditory, visual, and intellectual elements in the context of real problems can overcome learning limitations. The implications of this research indicate that the SAVI learning model, oriented to contextual problems, can serve as a strategic alternative in science learning.